Thinking in time the uses of history for decision-makers - Neustadt, Richard E. (New York Free Press, 1986)
Two noted professors offer easily remembered rules for using history effectively in day-to-day management of governmental and corporate affairs to avoid costly blunders. ?An illuminating guide to the use and abuse of history in affairs of state?
Includes index.
Keywords: Decision making --Case studies